Enhancing Primary Students’ Achivement in Civic Education with Talking Stick Approach - Nurmi, Nurmi; Putra, Hadi; Nursida, Penti; Mahbubah, Khoiro; Hermita, Neni (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This study aims to improve 3rd grade students’ science learning outcomes by learning to use visual multimedia. This research method uses classroom action research. The subject of this research was the third grade students of second semester of elementary school which conducted 30 students. Based on the results of research by using visual media, it have been found that the improvement learning outcome, seen from the initial average score before the action of 3rd grade class students from 65.5 to 83.83. The results of this study indicate that with the use of visual media can improve student learning outcomes.